Genetic Evolution Characteristics of Genotype G57 Virus, A Dominant Genotype of H9N2 Avian Influenza Virus - Wang, Jinfeng; Jin, Xuanjiang; Hu, Jingkai; Wu, Yifan; Zhang, Mengmeng; Li, Xiao; Chen, Jianglin; Xie, Shumin; Liu, Jing; Qi, Wenbao; Liao, Ming; Jia, Weixin (Frontiers in Microbiology, 2021)
This study aimed to investigate the genetic evolution of the H9N2 avian influenza virus (AIV). Whole genome phylogenetic trees were constructed based on 306 H9N2 avian influenza strains collected in China from 2014 to 2019. The results showed that eight gene sequences were clustered separately according to their dominant clades, and a total of 10 genotypes were identified (seven of which were novel types). Among them, G57 genotype was confirmed as the most prevalent genotype with a frequency of 94%. In China, the G57 genotype of H9N2 first emerged in 2007, and then became the most common genotype in 2013. Therefore, the nucleotide substitution rates of G57 genotype in HA and NA genes collected from 2007 to 2019 were estimated, and the positive selection pressure sites in the same data set were measured. Taking 2013 as the boundary, the time period was divided into two periods: 2007–2012 and 2013–2019. From 2007 to 2012, multiple genotypes coexisted and could bear the pressures from both nature and environment; while G57 genotype was still in the adaptation stage, subjected to less selection pressure and in the process of slow evolution. However, from 2013 to 2019, G57 became the dominant genotype, and most of the external pressure reacted on it. Moreover, G57 genotype showed better adaptability than other genotypes. From 2013 to 2019, the nucleotide substitution rates of the HA gene were increased, and the positive selection pressures on HA and NA genes were stronger compared to those from 2007 to 2012. To sum up, the absolutely dominant G57 genotype exhibited a relatively constant genotype frequency and experienced adaptive evolution and natural selection simultaneously during the monitoring period. Therefore, urgent attention and diligent surveillance of H9N2 avian influenza virus are becoming increasingly important.